Is the Relationship between Pattern Recall and Decision-Making Influenced by Anticipatory Recall?. Issue 11 (November 2013) - Gorman, Adam D.; Abernethy, Bruce; Farrow, Damian
The present study compared traditional measures of pattern recall to measures of anticipatory recall and decision-making to examine the underlying mechanisms of expert pattern perception and to address methodological limitations in previous studies where anticipatory recall has generally been overlooked. Recall performance in expert and novice basketball players was measured by examining the spatial error in recalling player positions both for a target image (traditional recall) and at 40-ms increments following the target image (anticipatory recall). Decision-making performance was measured by comparing the participant's response to those identified by a panel of expert coaches. Anticipatory recall was observed in the recall task and was significantly more pronounced for the experts, suggesting that traditional methods of spatial recall analysis may not have provided a completely accurate determination of the full magnitude of the experts' superiority. Accounting for anticipatory recall also increased the relative contribution of recall skill to decision-making accuracy although the gains in explained variance were modest and of debatable functional significance.